Peningkatan Kemampuan Desain Media Pembelajaran Bagi Guru SD Gugus 3 Kecamatan Pallangga Kabupaten Gowa - Rosdiana Ngintung; Nani Kurnia; Dewi Puspitasari; Anto Sukamto; Ilma Wulansari; Ristiana, Evi (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
Elementary school teachers as professional educators who act as facilitators in learning are required to be creative in exploring the potential of learning resources and media in their environment so that they can teach their students in a quality manner. It is necessary to increase the ability of teachers in designing media, elementary school teachers in cluster 3 in general already mastered Canva, but needs further improvement by adding Canva's Artificial Intelligence (AI) and Chat GPT. This community service aims to improve the learning media design skills of training elementary school teachers through the design of learning media with AI and GPT chat. As many as 25 teachers with different teaching backgrounds received material on how to design instructional media and carried out independent practice accompanied by a service team. Evaluation was carried out by means of observation, interviews, and giving questionnaires. The evaluation results show that this training succeeded in increasing the participants' design skills with a proportion of 88%, and the potential for using Canva to design learning media by 90%.